Handbook of research on power and energy system optimization - Kumar, Pawan; Singh, Surjit; Ali, Ikbal; Ustun, Taha Selim (Advances in computer and electrical engineering (ACEE) book series, 2018)
"This book explores how several optimization techniques involving extensive search, analytical approach and the computational or artificial intelligence. It also explores computational intelligence based on nature inspired meta-heuristic approaches are finding wider acceptance for optimization of discrete problems particularly for large systems with no fixed solution under different operating conditions"...